2019
DOI: 10.1093/rheumatology/kez297
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and distribution of various rheumatic disorders associated with checkpoint inhibitor therapy

Abstract: Immune checkpoint inhibitors have advanced the treatment paradigm of various cancers, achieving remarkable survival benefits. However, a myriad of immune-related adverse events (irAE) has been recognized in almost every organ system, presumably because of persistent immune system activation. Rheumatic symptoms such as arthralgia or myalgia are very common. More specific irAE are increasingly being reported. The most frequent ones are inflammatory arthritis, polymyalgia-like syndromes, myositis and sicca manife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 110 publications
0
34
1
3
Order By: Relevance
“…However, a minority of patients develop more pronounced pain with inflammatory features, such as morning stiffness as well as joint swelling suggestive of arthritis. Arthritis prevalence does not seem to exceed 7% [9]. Terminology and heterogeneity issues exist, making estimation of true prevalence difficult.…”
Section: Inflammatory Arthritismentioning
confidence: 99%
See 3 more Smart Citations
“…However, a minority of patients develop more pronounced pain with inflammatory features, such as morning stiffness as well as joint swelling suggestive of arthritis. Arthritis prevalence does not seem to exceed 7% [9]. Terminology and heterogeneity issues exist, making estimation of true prevalence difficult.…”
Section: Inflammatory Arthritismentioning
confidence: 99%
“…Median time to symptom onset following ICI initiation did not exceed the period of three months. Review of the literature, however, highlights the clinical variability of ICI-exposed patients developing arthritis [9,13]. In a recent review of case reports and case series [14], 90 cases of de novo ICI-related arthritis were identified in a period of 18 months.…”
Section: Inflammatory Arthritismentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of immunotherapy on the bone of patients with PCa has only begun to be explored. It is well established that immune checkpoint inhibitors result in immune‐related rheumatic and musculoskeletal adverse events, such as inflammatory arthritis, arthralgia, and myalgia 77,78 . Yet only recently has a study found that immunotherapies result in SREs.…”
Section: Discussionmentioning
confidence: 99%